Comparison of operative microscope and exoscope for execution of microanastomoses on an artificial model - Calloni, T.; Carone, G.; Cavaliere, M.; de Laurentis, C.; Bussa, M.; Antolini, L.; Nicolosi, F.; Carrabba, G. G.; Fontanella, M. M.; Cenzato, M.; DiMeco, F.; Acerbi, F.; et al. (Frontiers in Surgery, 2025)
IntroductionWhile the improved ergonomics, depth of field, and freedom of movement offered by Exoscopes compared to Operative Microscopes are well established, their value in surgical education and training is often mentioned but remains poorly documented.MethodsIn this study, we used a using a slightly modified version of the NOMAT score to compare the microvascular anastomoses on an artificial model made using traditional Operative Microscopes and the Orbeye 4K 3D Exoscope. Each participant performed the task 3 times.ResultsThe results showed that microscope users initially scored higher in several aspects, likely due to greater prior familiarity with the device. However, by the third repetition, the differences were no longer significant, demonstrating that the Exoscope is not inferior to the traditional Microscope in laboratory training. Moreover, the Exoscope group exhibited a faster learning curve for specific skills, highlighting its potential for early adoption by young surgeons.DiscussionThese findings emphasize the educational promise of Exoscopes, particularly in facilitating a smooth transition from traditional microscopes. However, further studies with larger sample sizes and extended training periods are needed to validate these conclusions.